Effects of bath composition and current density on the electrodeposition of Fe-Ni alloy on copper substrate and the property of deposited alloy (Bangladesh Journal of Scientific and Industrial Research, 2013)
One simple and six complex baths are used to electrodeposit Fe-Ni alloy coating on copper substrate. All baths contain the same 1.04 Ni/Fe ratio. In addition to NiSO4.7H2O, FeSO4.7H2O, H3BO3 used in simple bath, the complex baths contain Ascorbic acid, Saccharin and Citric acid in different ratios. Electrodepositions have been carried out in the bath pH and constant current density range of 1 - 2.6 and 20 - 140 mA/cm2, respectively. Anomalous nature of Fe-Ni alloy electrodeposition is suppressed in the complex baths. Microhardness as well as corrosion resistance of coating increased with increasing %Ni content in the deposit. The morphology of the Fe-Ni films obtained from simple baths is characterized by coarse-grained, non-smooth surface with presence of microcracks onto it. Coatings from complex baths are finegrained with smooth surfaces. Bangladesh J. Sci. Ind. Res. 47(4), 379-386, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.8699